ANALISIS PENERIMAAN TEKNOLOGI SISTEM INFORMASI JASA KONSTRUKSI PADA DINAS PUPR KABUPATEN WAY KANAN MENGGUNAKAN METODE TAM - Ahyar, Ahyar; Hasibuan, M.Said (LP2M Institut Informatika Dan Bisnis Darmajaya, 2025)
In its daily operations, the Public Works and Spatial Planning Office (Dinas PUPR) of Way Kanan Regency utilizes several systems as tools to assist with activities and store important institutional data. One of the systems used in the Dinas PUPR office is the Construction Services Information System, which functions as a provider of construction services data and information, supported by information and telecommunication technology, and regulated by legal provisions. This system allows the Head of the Office or the Regent of Way Kanan Regency to easily monitor the ongoing projects handled by Dinas PUPR.Hypothesis 1 (Attitude Toward Using → Behavioral Intention to Use the Construction Services Information System of Dinas PUPR Way Kanan Regency)Based on the coefficient parameter Attitude Toward Using → Behavioral Intention to Use (original sample) of 0.631, there is a POSITIVE influence between these two variables. This indicates that the higher the Attitude Toward Using, the better the Intention to Use. Additionally, the T-statistic value of 3.996 is considered SIGNIFICANT, as it is greater than the T-table value (3.996 > 1.96). Thus, the hypothesis is accepted.Based on the coefficient parameter Attitude Toward Using → Behavioral Intention to Use (original sample) of 0.157, there is a NEGATIVE influence between these two variables. This means that a lower Attitude Toward Using leads to a lower Behavioral Intention to Use. Furthermore, the T-statistic value of 1.116 is considered NOT SIGNIFICANT, as it is less than the T-table value (1.116 < 1.96). Thus, the hypothesis is not accepted